Managers as designers in the public services : beyond technomagic - Wastell, David (Triarchy Press, 2011)
Public services under pressure Around the world, public services are under pressure from all directions: required to be cheaper, more efficient, more effective, less wasteful, more 'joined-up', more in touch with people's needs, leaner, less bureaucratic ... Whether public services are seen as Beauty (in Scandinavia, say) or The Beast (by the US Tea Party, for example), they face increased demands and reduced resources almost everywhere. Inevitably, one solution that has been turned to has been IT. (This is particularly true of local government, the health and education sectors, and the emergency services, which have invested heavily in IT 'solutions'.) New computer systems - often alongside merged back office functions, economies of scale and outsourcing - are regularly expected to offer a better and faster service at lower cost. Imposed IT solutions often make things worse David Wastell calls our continuing (and unwarranted) faith in imposed, computer-based solutions 'technomagic'. In Managers as Designers in the Public Services, he draws startling parallels between our expectations of IT solutions in the public sector and the expectations of Melanesian canoe-builders who use bunches of grass to drive heaviness and slowness out of their boats. He then uses detailed examples and case studies from the UK and USA to show just how misplaced has been our reliance on IT-based 'solutions' to public sector problems. But this book is much more than an informed and devastating critique of the UK's Integrated Children's System, US educational reform and the high-profile failure of the London Ambulance Service. Applying Design Thinking to IT in public services David Wastell goes on to develop and apply the principles of Systems Thinking and Design Thinking to show how we need a 'design revolution' in the public services. Rather than monitoring, measuring and controlling, public sector managers need to see themselves as designers, whose job it is to reshape work systems and the whole workplace. He then uses two further case studies to give concrete examples of Design Thinking in action, with highly positive outcomes from design-based approaches to IT innovation.